A Metabolism‐Oriented Strategy for Systematic Analysis of the Pharmacological Material Basis of Classic Traditional Chinese Medicine Formulas: Taking Wuao Sanzi Decoction as an Example - Jin‐Jin Liao; Yang‐Dan Liu; Lan‐Ying Gao; Gui‐Zhong Xin; Yuan Cao; Zi‐Qi Shi (Journal of Separation Science, 2026)
ABSTRACT Deciphering the pharmacodynamic material basis of classical traditional Chinese medicine (TCM) formulas remains a critical challenge, owing to their multicomponent nature, multitarget interactions, and intricate in vivo metabolic fates. To address this issue, a metabolism‐oriented strategy was established and applied to Wuao Sanzi Decoction (WASZD), a classic TCM formula for respiratory diseases such as asthma. Ultra‐high‐performance liquid chromatography coupled with quadrupole time‐of‐flight tandem mass spectrometry was used for systematic analysis of the chemicalome, in vivo prototypes, metabolites, and tissue distribution of WASZD. A total of 200 chemical components were identified in vitro, including 102 flavonoids, 29 triterpenoids, 10 steroids, 14 organic acids, and 45 other compounds. Further, 91 prototypes and 212 metabolites in vivo were characterized in biological samples of rats. Key metabolic pathways involved phase I reactions (reduction, oxidation, and demethylation), phase II reactions (glucuronidation, methylation, and sulfation), and gut microbiota‐mediated ring cleavage of flavonoids, which generated bioactive small‐molecule phenolic acids. Tissue distribution analysis revealed that prototypes and metabolites were predominantly enriched in the ileum, colon, liver, kidney, and lung, with flavonoids and their metabolites identified as the most abundant components, suggesting they are the core bioactive candidates of WASZD. This study not only putatively clarifies the pharmacodynamic material basis of WASZD but also establishes a reproducible technical framework for decoding the complex in vivo behavior of multi‐component TCM formulas, facilitating their modernization and rational clinical application.